THE ROLE OF THE ACEH ULEMA COUNCIL AND MUSLIM CONSUMER PROTECTION IN HALAL CERTIFICATION OF FOOD AND BEVERAGE PRODUCTS FROM THE PERSPECTIVE OF SHARIA ECONOMIC LAW - Laily Saprina; Soraya Devi; Misran (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2026)
This article aims to analyse the role of the Aceh Ulama Council (MPU) in the implementation of halal certification for food and beverage products, and its relation to the protection of Muslim consumers, from the perspective of Islamic economic law. The research method used is qualitative, with a juridical-empirical approach, drawing on literature studies, related regulations, and interviews with consumers and the Aceh MPU LPPOM. The results of the study show that although Aceh Qanun No. 8 of 2016 on the Halal Product Guarantee System has been in effect since 2016, its implementation remains suboptimal. This can be seen from the large number of food and beverage products, including imported products, that are circulating without halal labels. LPPOM MPU Aceh plays a role in the halal certification process through administrative checks, laboratory testing, and certificate issuance. Still, its implementation is hampered by low consumer awareness, limited business compliance, and a lack of coordination among relevant institutions. From a Sharia economic law perspective, the existence of halal certification is not only a form of protection for Muslim consumers but also the implementation of the halalan thayyiban principle to safeguard the interests of the people and create a sense of security in the consumption of everyday products. Therefore, strengthening regulations, increasing the capacity of business actors, and continuously educating the public are essential steps to raise awareness of the importance of halal products and achieve the objectives of Islamic economic law optimally.